2017
DOI: 10.1080/10942912.2017.1347673
|View full text |Cite
|
Sign up to set email alerts
|

Structural and surface properties of whey protein from buffalo milk as influenced by exopolysaccharide

Abstract: The influence of exopolysaccharide (EPS) on the structure of whey protein (WP) molecules at different pH and ionic strengths was investigated using fluorescence and circular dichroism (CD) spectroscopy. The WPs were separated using 0.2 mol/L glacial acetic acid, which has been proved to maintain to the maximum extent the native structure of WP molecules. The interaction between WP and EPS was significantly influenced by the ionic strength and pH. The presence of NaCl reduced the repulsion and aggregation of WP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As such, the formation of EPS occurring in situ in the matrix may cause similar phase separations once the EPS concentration reaches a critical value. These phenomena depend not only on polymer concentration, but on structural properties, and occur, for example, more readily if polymers have high molecular weights, carry high similar charges, and differ in flexibility and ability to assume different configurations (Zhao, Li, Zhao, & Li, 2017). Studies have shown segregative phase separation phenomenon can be a major contributor to a soft texture and spreadability, since network forming polymers (e.g., proteins) are hindered in their ability to crosslink and form percolating structures.…”
Section: Mechanistic Insights and Structure–function Relationshipsmentioning
confidence: 99%
“…As such, the formation of EPS occurring in situ in the matrix may cause similar phase separations once the EPS concentration reaches a critical value. These phenomena depend not only on polymer concentration, but on structural properties, and occur, for example, more readily if polymers have high molecular weights, carry high similar charges, and differ in flexibility and ability to assume different configurations (Zhao, Li, Zhao, & Li, 2017). Studies have shown segregative phase separation phenomenon can be a major contributor to a soft texture and spreadability, since network forming polymers (e.g., proteins) are hindered in their ability to crosslink and form percolating structures.…”
Section: Mechanistic Insights and Structure–function Relationshipsmentioning
confidence: 99%